ANALISIS PENGARUH FAKTOR INTERNAL (INTELEGENSI, MINAT, BAKAT, MOTIVASI, USIA) DAN FAKTOR EKSTERNAL (LINGKUNGAN, PENDIDIKAN, PENGALAMAN, PELATIHAN) TERHADAP PEMAHAMAN PEMBIAYAAN MUDHARABAH DAN MURABAHAH (STUDI PADA BMT DI KABUPATEN KEBUMEN) - Kusuma, Wati (Fokus Bisnis, 2013)
This study was conducted at Baitul Maal Wa Tamwil (BMT) employee who join in BMT Association of Kebumen Regency. This study is entitled âThe Effect Analysis of Internal Factors (Intelligence, Interests, Talent, Motivation, Age) and External Factor (Environment, Education, Experience, Training) toward Understanding of Mudharaba and Murabahah